Exploring the challenges of task-centred training in obstetric anaesthesia in the operating theatre environment. (August 2019) - Goy, R.W.L.; Ithnin, F.; Lew, E.; Sng, B.L.
Highlights: Task-centred learning can be impacted by challenges in the operating theatre. Challenges include clinical, socio-cultural factors and interprofessional practice. Dedicated trainee lists, a reflective diary and in-situ simulation can be considered. Research is needed on the influence of clinical risks on teaching behaviours. Abstract: Background: Task-centred learning forms the basis of procedural training in obstetric anaesthesia. We observed that our residents were not building their competence from experiential practice in the operating theatre. We used a broad-based framework to explore the challenges encountered by the residents and clinical supervisors in the learning and teaching of obstetric anaesthesia. Methods: The study was conducted at the KK Women's and Children's Hospital, Singapore, from 1 December 2016 to 30 June 2017. A semi-structured interview format was used in the focus group and individual interviews. Information collection continued until data saturation was reached. The interviews were analysed and the challenges were identified. Fourteen residents and five clinical supervisors participated in the focus group and individual interviews respectively. Findings: The operating theatre constituted a stressful learning and teaching environment for the participants. Five categories of challenges were identified: (1) clinical conditions, (2) concerns about maternal risk and outcomes, (3) reluctance of the residents to vocalise their learning needs, (4) poor feedback, and (5) lack of opportunities for inter-professional practice. These collective challenges reduced the quality of task-centred learning and the effectiveness of supervisor teaching. We described some strategies to overcome these challenges (dedicated trainee lists, obstetric anaesthesia reflective diary, active mentoring system and in-situ simulation). Conclusions: Our study described the challenges of obstetric anaesthesia training in the operating theatre environment in an Asian healthcare setting. Research is needed on the influence of supervisors' concern about maternal risks and their teaching behaviours.